Process of budgetary programming and its influence on the use of public funds in the Ite Distrital Municipality, 2017 - Alca Tito, Ederth Christian (2019)
Otherwise they will be observed by the Institutional Control Body; Therefore, the purpose of the study is to: Determine how the budget programming process influences the use of public funds in the District Municipality of Ite, 2017. The level of investigation is explanatory. The population was constituted by the registries of the budgetary programming and the use of the public funds, of the year 2017, being a total of 60 registries. It was not necessary to obtain a sample. The instrument used was the document analysis guide. The results determined that the budgetary programming process significantly influences the use of public funds in the District Municipality of Ite, 2017, due to the fact that in the programmed and executed budget of income and expenses by source of financing in soles corresponding to the budget year 2017 of the District Municipality of Ite, in what refers to the programmed income budget is in PIM S /. 26 347 155 soles and a collection of S /. 27 303 756 soles, which represents 103.6%, exceeding the amount programmed; in terms of expenses, it was programmed in PIM S /. 26 347 155 soles, reaching S /. 20 139 382 soles, which represents 76.4% of the programmed budget.